Ability plants Mathiola incana & Petunia intergrifolia in Absorption some heavy elements and effect in growth characterisitcs - Riham H. Ahmed; Ibrahim A Alsadawi; Gihad T. Mahal (Tikrit Journal of Pure Science, 2023)
This study was carried out in green house & Laboratories of biology department of college science / Baghdad university for the peroid 1/11/2014 – 1/3/2015, it aims to test the ability of ornamental plants(Gillyflower and petunia) on heavy metals uptake and their effect in some physiological characteristics leaves number and plants high and a chlorophyll and b chlorophyll and total chlorophyll  Results also showed that, addition of lead and cadmium to the soil at studied concentrations caused areduction in growth mean and leaves number , because of lead additio Gillyflower and petunia high reduced to (28, 29) cm compared to control (35, 36)cm respectively, and also cadmium addition caused areduction in a Gillyflower and petunia high, plants high was (32, 28)cm respectively compared to control(43, 34)cm respectively Results that obtained from this study showed areduction in a ,b and total chlorophyll , at (200) ppm lead treatment a ,chlorophyll for both plants and petunia were (0.35, 0.37) mg.gm -1 compared to control (0.67, 0.73) mg.gm -1 respectively, while cadmium effect on Gillyflower and petunia chlorophyll at (60) ppm treatment were(0.33, 0.36) mg.gm-1  compared to control (0.69, 0.65) mg.gm -1 respectively b. chlorophyll reduced in Gillyflower and petunia by the effect of lead element at (200)ppm to (0.28) mg.gm -1  for both plants compared to control which reaches (0.47, 0.45) mg.gm-1  respectively, while cadmium effect reduced b ,chlorophyll at (60) ppm to (0.38,0.21) mg.gm-1compared to control (0.46, 0.48) mg.gm-1 respectively. Total chlorophyll also reduced by effect of lead element on both plants, Gillyflower and petunia at (200)ppm treatment to (0.47) mg.gm -1  for both plant compared to control treatment which reaches (0.93, 1.54) mg.gm -1  respectively, while cadmium effect at (60)ppm reduced total chlorophyll to (0.28 , 0.30) mg.gm -1  compared to control treatment which reaches (1.02 , 0.90) mg.gm -1  respectively.